Women report more symptoms and impaired quality of life: a survey of Finnish COVID-19 survivors. Issue 1 (2nd January 2022) - Lindahl, Anna; Aro, Miia; Reijula, Jere; Mäkelä, Mika J.; Ollgren, Jukka; Puolanne, Mervi; Järvinen, Asko; Vasankari, Tuula
Abstract: Background: The long-term sequelae after COVID-19 are not yet fully known. Our aim was to evaluate subjective symptoms and quality of life in Finnish hospitalized COVID-19 patients at six months follow-up. Methods: Hospitalised adult patients with laboratory-confirmed SARS-CoV-2 infection from March to June 2020 were recruited. We conducted a survey on demographics and comorbidities, ten specific symptoms, and a RAND-36 quality of life questionnaire six months after hospital discharge. We collected clinical data manually from medical records. Results: 101 patients (54 male) out of 246 invited completed the survey. Their median age was 60 years, and the mean hospital length of stay was 15 d. Most patients (90%) experienced symptoms, the most common of which were tiredness (88%), fatigue (79%), sleeping problems (76%), and dyspnoea (70%). In regard to gender, women showed a shorter time of hospitalization ( p  = .048) and lower peak flow of supplementary oxygen ( p  = .043). Women reported more frequently dyspnoea, fatigue, tiredness, sleeping problems, and mood problems ( p  = .008–.033), and a lower quality of life in seven of eight dimensions ( p  < .001–.015). Five explanatory variables for the reduced quality of life were identified in multivariate analysis: age, female sex, BMI, sleep apnoea, and duration of mechanical ventilation. Of the patients who worked full-time before COVID-19, 11% had not returned to work. Conclusions: Most patients experienced symptoms six months after hospital discharge. Women reported more symptoms and a lower quality of life than men. These findings highlight the differences in recovery between men and women and call for active rehabilitation of COVID-19 patients.